ANALISIS KELAYAKAN INVESTASI SAHAM PERUSAHAAN (STUDI KASUS PADA PT. KINO INDONESIA.TBK) - Aldrin Alexander (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
Analysis of Stock Investment Feasibility at PT. Kino Indonesia,Tbk. This research aims to analyze the feasibility of stock investment at PT. Kino Indonesia,Tbk., with growth analysis, profitability, liability and stock valuation. Using the case study method and quantitative approach, the result of the analysis show that the fundamental and profitability of the Company is in bad condition, even though it’s share price is below fair value. Investors are advised to monitor the company's future efforts, to improve their performance. Cause, it’s far better to buy a wonderful company at a fair price, than a fair company at a wonderful price.